Classical signs of Keratoconus - Josephine S. Christy; Shivraj Tagare (Delhi Journal of Ophthalmology)
Keratoconus is a bilateral progressive disease of unknown etiology characterized by gradual corneal thinning, steepening and ectasia. Though corneal topography plays a significant role in its diagnosis, early identification with clinical signs can greatly improve the visual outcome with appropriate management. This PG snippet elaborates on the classical signs of keratoconus by clear demonstration with slit lamp pictures.